2019
DOI: 10.1186/s13052-019-0738-3
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic pancreas in the gastrointestinal tract in children: a single-center experience and a review of the literature

Abstract: BackgroundHeterotopic pancreas, that is the abnormal localization of a well-differentiated pancreatic tissue, is a rare occurrence in pediatric patients. Most lesions are found incidentally; in some circumstances, the presence of heterotopic pancreas may cause gastrointestinal symptoms, such as obstructive symptoms or bleeding.Patients and methodsThe clinical notes of patients with histological diagnosis of heterotopic pancreas treated at Meyer Children’s Hospital between 2009 and 2017 have been retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
1
21
0
3
Order By: Relevance
“…HP has been reported at all ages including children, average being 45 years. 5,[9][10][11] In our study, the age ranged from one day to 48 years (average 27.5 years). Dolan et al have reported the largest series of 214 cases of HP at Mayo clinic from 1952 to 1974.…”
Section: Discussionmentioning
confidence: 99%
“…HP has been reported at all ages including children, average being 45 years. 5,[9][10][11] In our study, the age ranged from one day to 48 years (average 27.5 years). Dolan et al have reported the largest series of 214 cases of HP at Mayo clinic from 1952 to 1974.…”
Section: Discussionmentioning
confidence: 99%
“…Литературные данные об эктопии поджелудочной железы свидетельствуют о редкости данного порока развития, что зачастую ведет к диагностическим и лечебно-тактическим ошибкам. Сложность диагностики и лечения ЭПЖ заключается в скудности и неспецифичности клинических проявлений заболевания [1][2][3][4].…”
Section: Discussionunclassified
“…В отсутствие осложнений ЭПЖ может длительное время протекать бессимптомно и выявляться лишь при диагностической лапароскопии или открытом оперативном вмешательстве по поводу другой патологии органов брюшной полости [9][10][11], аналогично представленному в данном наблюдении. Отсутствие специфических клинических проявлений, сложность диагностики в некоторых случаях становятся причиной позднего выявления порока развития, которое в дальнейшем выявляется у взрослых пациентов [4,12,13]. Диагностика ЭПЖ у детей на основании клинических и рентгенологических данных весьма сложна.…”
Section: Discussionunclassified
“…Patients’ age as a parameter for symptoms was reported by Persano et al [ 20 ]. In his study, which included 14 pediatric patients, seven patients (50%) were symptomatic and the rest were asymptomatic.…”
Section: To the Editormentioning
confidence: 99%